Sodium‐Ion Batteries: Recent Progress in Advanced Organic Electrode Materials for Sodium‐Ion Batteries: Synthesis, Mechanisms, Challenges and Perspectives (Adv. Funct. Mater. 11/2020). (10th March 2020) - Yin, Xiuping; Sarkar, Samrat; Shi, Shanshan; Huang, Qiu‐An; Zhao, Hongbin; Yan, Liuming; Zhao, Yufeng; Zhang, Jiujun
Abstract : In article number 1908445, Yufeng Zhao and co‐workers review the research progress with regards to electrode materials of organic sodium‐ion batteries, ranging from small molecules to organic polymers, with a focus on the molecular structure design/modification, electrochemical behavior, and corresponding charge‐storage mechanism.